THE CONCEPT OF SPACE INHABITATION: "NEARLY ADEQUATE" (Case: Row House in Petogogan, South Jakarta) - Olivia Yuni Rahayu; Popi Puspitasari; Indartoyo Indartoyo (International Journal on Livable Space, 2016)
ABSTRACTRISHA system of Petogogan’s row house in South Jakarta, is applied to solve the problem of slum settlement area along the Krukut river bank. The inhabitants of the row house have their own assessment in term of the need level for living. By using quantitative -QUALITATIVE approach, it is uncovered that the inhabitants have the concept of ‘nearly adequate’ to maintain the occupying space which actually does not quite accommodate their daily activities. However, they arrange the space in certain ways to meet their needs. ‘Nearly adequate’ concept consists of three unique ideas: flexible, economic and it manifests the concept of sincerity. At the end of this article will be presented about a model of that ‘nearly adequate‘ concept.Keywords: Row house, level of need, ‘nearly adequate’ concept.